1965
DOI: 10.1002/ajpa.1330230315
|View full text |Cite
|
Sign up to set email alerts
|

Numerical aberrations in the permanent teeth of grade school children in Jerusalem

Abstract: An epidemiologic survey on the occurence of hypo-and hyperdontia was carried out among the 28,000 grade school children of Jerusalem. While the first condition was more prevalent among girls, boys had more supernumery teeth.The rate of both anomalities was higher in children belonging to Oriental ethnic groups than in children of European origin, and in Israelis of second generation. The maxilla was more often involved than the mandible, and the tooth most often lacking was the maxillary lateral incisor. Most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
30
1
1

Year Published

1967
1967
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 12 publications
7
30
1
1
Order By: Relevance
“…Studies in Europe, Australia, and North America reported a higher incidence of developmental absence of permanent teeth in females than in males [8,9,12,29], which is consistent with the present findings of a malefemale ratio of 1:1.4. Consistent with other studies, this study indicates a higher frequency of CMT in the maxilla than in the mandible [13,14,21,26,30,31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Studies in Europe, Australia, and North America reported a higher incidence of developmental absence of permanent teeth in females than in males [8,9,12,29], which is consistent with the present findings of a malefemale ratio of 1:1.4. Consistent with other studies, this study indicates a higher frequency of CMT in the maxilla than in the mandible [13,14,21,26,30,31].…”
Section: Discussionsupporting
confidence: 92%
“…The overall prevalence of hypodontia ranges from 0.3 to 11.3% in different regions and populations [7][8][9][10][11][12][13][14][15][16][17][18]. Oligodontia is very rare [19].…”
Section: Introductionmentioning
confidence: 99%
“…The wide range of frequency rates of hypodontia can be attributed to differences in the methods of sampling and examination and the distribution of age, sex, and racial origin of the subjects. Many studies have demonstrated that there was no consistent finding as to which jaw has more missing teeth (4,7,9,12,(17)(18)(19). However, Chung et al (8) found that hypodontia was significantly more in the mandible.…”
Section: Discussionmentioning
confidence: 99%
“…One more theory, well supported in the literature, is the hyperactivity theory, suggesting that the hyperactivity of dental lamina is the reason for supernumerary teeth formation [12]. Genetics are also instrumental for the occurrence of supernumerary teeth, as these anomalies are more common in the family of affected children than in the general population [13]. Few syndromes like Hallermann-Streiff's syndrome, Gardner's syndrome, Cleidocranial dysplasia, cleft lip and palate, oro-facial digital syndromes, etc.…”
Section: Introductionmentioning
confidence: 99%